Is Malaysia exempted from the impossible trinity? An empirical analysis for an emerging market - Ewe, Ghee Lim; Soo, Khoon Goh (Routledge, Taylor & Francis Group, 2016)
This paper estimates offset and sterilization coefficients in Malaysia with the objective to assess the relevance of the Impossible Trinity for policy. The paper finds that Malaysia had scope for independent monetary policy in the short run; but in the longer run only under managed floating or capital controls. The loss of long-run monetary autonomy under peg/open capital was in line with the trinity, and may be one reason the peg was eventually abandoned for managed floating in year 2005. The results suggest that managed floating with sterilizations could be a viable monetary strategy for emerging markets facing volatile capital flows.